How do mutations and allosteric inhibitors modulate caspase-7 activity? A molecular dynamics study - ÖZBEK SARICA, PEMRA (TAYLOR & FRANCIS INC, 2019)
Caspases are members of a highly regulated aspartate-cysteine protease family which have important roles in apoptosis. Pharmaceutical studies focused on these molecules since they are involved in diseases such as cancer and neurodegenerative disorders. A small molecule which binds to the dimeric interface away from the binding site induces a conformational change that resembles the pro-caspase form of the molecule by shifting loop positions. The fluctuation mechanisms caused by mutations or binding of a ligand can explain the key mechanism for the function of that molecule. In this study, we performed molecular dynamics simulations on wild-type and mutated structures (C290N, R187M, Y223A, G188L and G188P) as well as allosterically inhibited structure (DICA-bound caspase-7) to observe the effects of the single mutations on intrinsic dynamics. The results show that previously known changes in catalytic activity upon mutations or allosteric ligand binding are reflected in corresponding changes in the global dynamics of caspase-7. Communicated by Ramaswamy H. Sarma
Keywords: caspase-7; collective motions; global dynamics; amino acid interaction energies; molecular dynamics simulations; GENERAL FORCE-FIELD; STRUCTURAL-CHANGES; CRYSTAL-STRUCTURE; PROTEIN; CHARMM; NETWORK; LOOP; AUTOMATION; ACTIVATION; MECHANISMS